Revision of the species of Centris (Xanthemisia) Moure, 1945 (Hymenoptera: Apidae: Centridini) from the Caribbean island - Vivallo, Felipe (Zootaxa, 2014)
A revision of the species of Centris subgenus Xanthemisia Moure from the Caribbean islands is presented. The species identified are C. aethiops Cresson, C. domingensis Dalla Torre nom. rev. and C. caymanensis, a new species from the Cayman Islands, Lesser Antilles. Figures, morphological characters of both sexes and the description of the male of C. domingensis are given. New distribution records and an identification key for the three species of the subgenus that occur in the Caribbean islands are also provided.